0024 Effects of chronic low-dose exposure to ionising radiation on physician micro-vascular structure revealed by nail fold capillaroscopy. (23rd June 2014) - Wild, Pascal; Gauron, Christine; Derock, Christian; Champion, Karine; Cohen, Pascal; Menez, Caroline; Tellart, Anne-Sophie; Thiel, Hélène; Grzebyk, Michel; Donadille, Laurent; Pennarola, Raffaele; Choudat, Dominique
Abstract : Objectives: The aim of this study was to assess the long term pre-clinical effects of low-dose radiation on the micro-vascular structure among interventional physicians whose hands are exposed to ionising radiation in their daily practice. Method: The study, approved by the ethics committee, included 186 radiation-exposed (surgeons, cardiologists and radiologists) and 35 unexposed physicians. The study participants filled in a questionnaire describing their present and past daily practice from which the present and cumulative radiation exposures were estimated. Their dermal microcirculation was assessed by capillaroscopy of the nailfold of 8 fingers -thumbs excluded- of each study participant. Two quantitative scores characterising respectively extravasation and morphological abnormalities were obtained based on post-hoc codings of seven semi-quantitative indices by five capillaroscopists. These assessments were randomised and were blind to the exposure. The effect of the radiation exposure on both features was modelled using multilevel proportional odds regression adjusted for potential confounders. Results: The exposure intensity of each act was greatest among surgeons but with a lesser number of acts. The mean estimated cumulated exposure was largest among radiologist and cardiologists. No effect of the exposure could be detected on the extravasation score. The morphological anomaly score increased significantly with duration of exposure and cumulative exposure indices among surgeons and interventional radiologists contrary to cardiologists among which no effect could be detected. Conclusions: Capillaroscopy showed significant effects of chronic low-dose exposure to ionising radiation on micro-vascular structure among exposed physicians but its interest for individual monitoring has not been demonstrated.